Counter-stereotypical pictures as a strategy for overcoming spontaneous gender stereotypes - Finnegan, Eimear; Oakhill, Jane; Garnham, Alan (Frontiers in Psychology, 2015)
The present research investigated the use of counter-stereotypical pictures as a strategy for overcoming spontaneous gender stereotypes when certain social role nouns and professional terms are read. Across two experiments, participants completed a judgement task in which they were presented with word pairs comprised of a role noun with a stereotypical gender bias (e.g. beautician) and a kinship term with definitional gender (e.g. brother). Their task was to quickly decide whether or not both terms could refer to one person. In each experiment they completed 2 blocks of such judgement trials separated by a training session in which they were presented with pictures of people working in gender counter-stereotypical (Experiment 1) or gender stereotypical roles (Experiment 2). To ensure participants were focused on the pictures, they were also required to answer 4 questions on each one relating to the character’s leisure activities, earnings, job satisfaction and personal life. Accuracy of judgements to stereotype incongruent pairings was found to improve significantly across blocks when participants were exposed to counter-stereotype images (9.87%) as opposed to stereotypical images (0.12%), while response times decreased significantly across blocks in both studies. It is concluded that exposure to counter-stereotypical pictures is a valuable strategy for overcoming spontaneous gender stereotype biases in the short term.